A comprehensive review on learning curve associated problems in endoscopic vein harvesting and the requirement for a standardised training programme. Issue 1 (December 2016) - Krishnamoorthy, Bhuvaneswari; Critchley, William; Venkateswaran, Rajamiyer; Barnard, James; Caress, Ann; Fildes, James; Yonan, Nizar
Abstract Endoscopic vein harvesting is becoming one of the most favourable vein harvesting techniques in multiple bypass coronary surgery, due to its short term post-operative benefits with high patient satisfaction. However, long-term graft patency has been both supported and questioned in the literature. Graft failure can be affected by harvesting methods and operator's experience. Endoscopic vein harvesting is associated with a learning curve period, during which the incidence of vein trauma is high due to unfamiliarity with the surgical technique. There is a paucity of structured learning tools for novice practitioners, meaning that training differs significantly between hospital centres. Inconsistent training methods can lead to poor surgical technique, which can have a significant impact on vein quality and stress level of the practitioner. In turn, this can lead to increased postoperative complications and longer surgical duration. The main aim of this literature review is to understand the impact of the learning curve on the vein conduit and whether there is a requirement for a standardised training programme for the novice practitioners.